Illinois! - Ross, Dana Fuller (Toronto New York Bantam Books, 1986)
As roughrider Toby Holt struggles to build a new life in nineteenth century Chicago, an old enemy and a former love bring upheaval, tragedy, and death in a tale set against the 1871 fire that devastated Chicago
89576
Keywords: Western